A Simulation of Four Stroke Marine Diesel Engines to Predict Internal Cylinder Characteristics - Nguyen, Quang Vinh; Le, Van Vang; Bui, Hong Duong (JST: Engineering And Technology For Sustainable Development, 2021)
This paper introduces a simulation of four stroke marine diesel engines. The submodel of a particular cylinder was carried out, based on the first law of thermodynamics, programmed by Matlab/Simulink program, which describes the relations among internal characteristics, including: cylinder performance parameters, heat release, heat loss and pressure. The heat release is based on the Wiebe function and the heat loss is based on the Woschni function to build submodels. From the result of the model, the indicated pressure of a single cylinder was taken, the brake power of the engine could be estimated through this pressure. The object of the simulation is a new engine, hence the technical documents and test records provided by manufacturer are sufficient. The model got the input parameters from this and the key outputs of model (example the brake power, peak combustion pressure, specific fuel consumption) were compared with the test records to adjust and make it more accurate. These gaps were not over 5%, therefore, this model can be used to predict key complicated internal cylinder characteristics, for example the pressure, temperature, and thermal efficiency of engines.